Biodegradable Brightness: Green Synthesis of Carbon Dots and Their Applications - Somaprakash, Nagarjun; Badiya, Pradeep Kumar (ACS applied engineering materials, 2025)
This review comprehensively explores the expanding field of carbon dot (CD) synthesis, emphasizing sustainable “green” methodologies that utilize natural precursors like plant extracts, biomass, and food waste. Differing from traditional, often toxic, chemical approaches, this study highlights the environmental and economic advantages of green synthesis, including reduced costs, enhanced stability, and eco-friendly production. The review delves into various green synthesis techniques, such as hydrothermal, microwave, and pyrolysis methods, showcasing their efficacy in producing high-quality CDs. A strategic focus is the characterization and diverse applications of these green-synthesized CDs. The strong fluorescence tunability and large surface area of these CDs enable highly sensitive detection of metal ions, pollutants, and micromolecules, making them ideal for environmental monitoring and real-time sensing. The review also inspects their biocompatibility, photostability, and low toxicity, which are critical for applications in targeted cellular and in vivo imaging as well as controlled drug delivery. The ability to encapsulate drugs within CDs, coupled with their fluorescence tracking capabilities, proposes a powerful tool for monitoring drug release and cellular uptake. In addition, the review deliberates the application of CDs in energy storage, where their high surface area and electrical conductivity heighten the supercapacitor performance. Their role in photocatalysis, including pollutant degradation, water purification, hydrogen production, and CO2 reduction, is also explored, highlighting their potential in sustainable energy solutions. This review distinguishes itself by addressing the limitations of the existing literature, which primarily focuses on chemical synthesis and specific applications. It uniquely integrates the concept of plasmonic CDs, achieved through surface modification and hybridization with metal nanoparticles, to enhance functionality in areas such as targeted therapies, diagnostics, and antibacterial applications. By consolidating current knowledge on green synthesis and expanding into advanced applications, this review aims to promote environmentally friendly alternatives and guide future research toward large-scale, sustainable CD production.